Randomised controlled trial of the efficacy of a metered dose inhaler with bottle spacer for bronchodilator treatment in acute lower airway obstruction. Issue 2 (11th August 2006) - Zar, H J; Streun, S; Levin, M; Weinberg, E G; Swingler, G H
Abstract : Background: Inhaled bronchodilator treatment given via a metered dose inhaler (MDI) and spacer is optimal for relief of bronchoconstriction. Conventional spacers are expensive or unavailable in developing countries, but there is little information on the efficacy of low-cost spacers in young children. Objective: To compare the response to bronchodilator treatment given via a conventional or a low-cost bottle spacer Methods: A randomised controlled trial of the efficacy of a conventional spacer compared with a bottle spacer for bronchodilator treatment in young children with acute lower airway obstruction. Bronchodilator treatment was given from an MDI via an Aerochamber or a bottle spacer. Clinical score and oximetry recording were carried out before and after 15 min of treatment. MDI–spacer treatment was repeated up to three times, depending on clinical response, after which nebulisation was used. The primary outcome was hospitalisation. Results: 400 children, aged (median (25th–75th centile)) 12 (6–25) months, were enrolled. The number of children hospitalised (n = 60, 15%) was identical in the conventional and bottle spacer groups (n = 30, 15% in each). Secondary outcomes including change in clinical score (−2 (−3 to −1)), oxygen saturation (0 (−1 to 1)) and number of bronchodilator treatments (2 (1 to 3)) were similar in both groups. Oral corticosteroids, prescribed for 78 (19.5%) children, were given to a similar number in the conventional (37 (18.5%)) and bottle spacer groups (41 (20.5%)). Conclusion: A low-cost bottle spacer is as effective as a conventional spacer for bronchodilator treatment in young children with acute obstruction of the lower airways.